Literature Review: Psikologis pada Penderita Diabetes Melitus - Syafyu Sari, Febria; Afnuhazi, Ridhyalla; Fitri Amalia, Rosa; Lidya Hendayani, Weni; Arfhan Anwar , Bobby (Pustaka Galeri Mandiri, 2025)
Diabetes mellitus (DM) is a chronic disease that is suffered throughout life. Diabetes sufferers are required to change their lifestyle and undergo routine treatment at high costs. Lifestyle changes trigger psychological distress that appears in the form of feelings of sadness, nervousness, despair, anxiety, feelings of depression, efforts made in vain & useless. This can interfere with the diabetes treatment process. Psychological stress can have an impact on the healing of diabetes. This literature review aims to determine the psychological analysis of diabetes mellitus sufferers. The method used in the literature review uses a literature database that is adjusted to the topic of discussion. The results of the psychological analysis and synthesis that occur in diabetes sufferers include stress, anxiety and depression. Its recommended that the health care team, especially mental health nurses, provide education and complementary therapy related to psychological distress that occurs in chronic sufferers